Evaluation of the influence of arsenic on embryonic development of zebrafish (Danio rerio) - Thuong Huyen, Nguyen Thi; Truc Dao, Tran Thi; Son, Hoang Nghia (Academia Journal of Biology, 2018)
Arsenic is one of heavy metal elements which is dangerous to human and aquatic animals. Accumulating in the body,arsenic causes serious damage to organ systems such as the nervous system, circulatory system, digestive system, reproductive system, ect and even cancer, skin cancer is the most common type. This study aims to evaluate the influences of Arsenic (As) concentrations on different stages in embryonic development of zebrafish (Danio rerio): blastura, gastrula, segmentation, pharyngula and hatching. After mating, embryos were exposed to As in the examined concentrations: 0, 20, 50, 80, 110, 140, 170, 200, 230, 260 µg/L in the Hank’s embryonic medium. It was observed that the survival rate of embryonic zebrafish decreased gradually corresponding to the increasing the concentration of As and the development stages of the embryo. However, examined concentrations of As in this study did not reach the threshold lethal concentration (LCt50) of embryos. With the increasing of examined As concentrations, the heartbeat increased linearly, the body turning beat of each stage decreased linearly. The highest heartbeat was 237.73±1.87 beat/min in 260 µg/L concentration while it was 197.60±2.20 beat/min in the control group (p < 0.05) in the hatching stage. The lowest body turning was 2.53 beat/min while it was 5.50 beat/min (p < 0.05) in the control group in the pharyngula stage. Moreover, the As prolonged the hatching duration and reduced the hatching rate of embryonic zebrafish, after 72 hour fertilization, the hatching rate was 77.78% in 260 µg/L concentration while it was 98.86% in the control group (p < 0.05).